2017
DOI: 10.5271/sjweh.3659
|View full text |Cite
|
Sign up to set email alerts
|

Intervention to diminish dehydration and kidney damage among sugarcane workers

Abstract: Strenuous work in hot environments is associated with negative impacts on biomarkers of kidney function over the workday and over five months. Appropriate access to water, rest and shade during work offers relief from high levels of heat stress and reduces effects on kidney function.Affiliation: University of Massachusetts Lowell, 7 Camden Place, Cambridge, MA 02138, USA. david_wegman@uml.eduThe following article refers to this text: 2018;44(1):1-2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
2
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(108 citation statements)
references
References 29 publications
2
98
2
6
Order By: Relevance
“…The start of the harvest, when workers acclimatize to the physically demanding work, was associated with the largest cross-shift differences in hydration and kidney function (47). In a waterrest-shade intervention study in El Salvador, the cross-shift decline in eGFR related to workload (tons cut); moreover, the intervention appeared to reduce cross-shift kidney function decline (48). In Guatemala, an ostensibly intense hydration regimen was implemented, but indicators of poor hydration were still associated with kidney function decline and biomarkers of kidney injury during the workday (49).…”
Section: Analytical Epidemiologic Studies Highlight Occupational Heatmentioning
confidence: 99%
See 2 more Smart Citations
“…The start of the harvest, when workers acclimatize to the physically demanding work, was associated with the largest cross-shift differences in hydration and kidney function (47). In a waterrest-shade intervention study in El Salvador, the cross-shift decline in eGFR related to workload (tons cut); moreover, the intervention appeared to reduce cross-shift kidney function decline (48). In Guatemala, an ostensibly intense hydration regimen was implemented, but indicators of poor hydration were still associated with kidney function decline and biomarkers of kidney injury during the workday (49).…”
Section: Analytical Epidemiologic Studies Highlight Occupational Heatmentioning
confidence: 99%
“…Cross-shift evaluations have been conducted in sugarcane cutters in Costa Rica, Nicaragua, El Salvador and Guatemala. Without exception, these studies concluded that cross-shift physiologic and biomarker changes were compatible with recurrent dehydration from strenuous work in hot environments (45)(46)(47)(48)(49)(50). Three studies examining multiple cross-shifts documented repeated dehydration over the day (45,47,48).…”
Section: Analytical Epidemiologic Studies Highlight Occupational Heatmentioning
confidence: 99%
See 1 more Smart Citation
“…diabetes mellitus tipo 2 e hipertensión arterial), se podría hablar de ERC de etiología desconocida. Para dicha condición se han descrito otros factores de riesgo como deshidratación crónica (frecuente en sujetos que trabajan en el campo) (22) , exposición a pesticidas (aunque la evidencia es limitada) (23,24) , e infección por leptospirosis (evidencia aún escasa) (25) . Estas causas, aunque secundarias en relación a los factores de riesgo preponderantes, se deben tener en mente para no sólo sospechar -y así descartar-ERC en pacientes con antecedentes de diabetes o hipertensión.…”
Section: Discussionunclassified
“…Diversos estudios han demostrado deshidratación en estos trabajadores durante la jornada y un deterioro de su función renal a lo largo de una temporada de cosecha. Según los resultados del Programa WE, -un estudio de intervención en cortadores de caña en El Salvador -, la provisión de agua, descanso y sombra parece detener el deterioro de la función renal durante la cosecha 10 . A nivel experimental se ha mostrado que ratones expuestos a calor sin poder hidratarse durante el día desarrollan daño túbulo-intersticial renal.…”
unclassified